A comparative analysis of shareholders' appraisal rights in Nigeria and South Africa - Eniola, Abimbola (Department of Commercial Law, 2020)
First, this study stems from the urge to bring clarity as to whether, in Nigeria, there is a statutory framework based on which shareholders can seek appraisal in relation to their shares at any point in time. This is significant in that the corporate statutes in both South Africa and Nigeria provide for similar mechanisms for the protection of minority shareholders in almost every respect including the prejudicial and oppression remedy, derivative actions, squeeze-outs and so on, excepting the appraisal rights. Whilst there is clarity as to the existence of the appraisal remedy provision in South Africa’s corporate statute, the same cannot be said of Nigeria’s corporate statute. Consequently, the primary goal of this study is to identify if there is a framework for the exercise of appraisal remedy in Nigeria’s corporate statute. In carrying out this study, this dissertation examines the various components of the appraisal right provision in South Africa in detail. This helps to provide an understanding around the structure and the rationale behind a standard appraisal right provision. It is based on this understanding that certain pre-identified provisions in Nigeria’s corporate statutes will be investigated with a view to identifying potential statutory framework bearing semblance to South Africa’s appraisal right provision.